Swedish municipality and place name register 1980 - Swedish municipality and placename register - Swedish telecom (Swedish telecom, 1984)
The file includes information about more than 130.000 Swedish place names, their location according to county, municipality and parish, designation, postal address and area code.

Data innehåller information om mer än 130 000 svenska ortnamn, deras placering i landet, kommun och län, adress och postnummer.
Svensk ortnamnsförteckning 1980
Keywords: Language and linguistics; Språk och lingvistik; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Human Geography; Kulturgeografi; Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik